Effects of dietary protein on growth and nutrient utilization in ornamental koi fish Cyprinus rubrofuscus (Lacepede, 1803) - Ahmad, Waqas; Ishtiaq, Abir; Khan, Naveed Ahmad; Abbas, Muhammad; Abbas, Zafar (Journal of Fisheries, 2025)
Ornamental fish farming is an expanding sector and determining the ideal dietary protein for fish growth is crucial for the success of fish farming in developing countries. In this study, the impact of varying dietary protein (DP) levels (25, 30, 35, 40, 45 and 50%) on the growth and feed conversion ratio (FCR) of koi fish (Cyprinus rubrofuscus) were assessed. The fish fed twice daily for 90 days at a rate of 5% of their body weight and growth parameters and FCR measured every 15 days. Results revealed that the highest weight gain (170.98 g) observed with the 35% DP diet (D-3), while the lowest gain (103.98 g) occurred with the 45% DP diet (D-5). The 35% DP diet also produced the specific growth rate (0.59±0.10), protein efficiency ratio (PER) 2.27±0.27 and feed efficiency percentage (FE%) 60.57±4.40, all of which were significantly higher (p < 0.05) than those from the other diets. The best FCR value of 1.65±0.12 was also found in the 35% DP diet (D-3), which was significantly lower (p < 0.05) than the others. Nutritionally, moisture and ash content was significantly lower (p < 0.05) in D-3 as compared to other diets. Additionally, dietary protein levels had a significant effect (p < 0.05) on final weight, specific growth rate, protein efficiency ratio and protein feed of C. rubrofuscus. These findings offer important insights into the optimal dietary protein level for C. rubrofuscus, which could help improve the commercial success of ornamental fish farming.